The Synthesis and Accumulation of Resveratrol Are Associated with Veraison and Abscisic Acid Concentration in Beihong (Vitis vinifera × Vitis amurensis) Berry Skin - Wang, Junfang; Wang, Shuqin; Liu, Guotian; Edwards, Everard J.; Duan, Wei; Li, Shaohua; Wang, Lijun (Frontiers in Plant Science, 2016)
Resveratrols are polyphenolic secondary metabolites that can benefit human health, and only occur in a few plant families including Vitaceae. It has been reported that abscisic acid (ABA) can induce veraison (the onset of grape berry ripening) and may induce the accumulation of resveratrol in berry skin. However, the relationships between ABA, veraison, the accumulation of anthocyanins and the accumulation of resveratrol in the berry are poorly understood. This study attempted to answer this question through an investigation of the effect of applied ABA and fluridone (a synthetic inhibitor of ABA) on the biosynthesis and accumulation of ABA, anthocyanin, and resveratrol in Beihong (Vitis vinifera × Vitis amurensis) berry skin. Under natural conditions, resveratrol concentration was very low before 91 DAA (days after anthesis), i.e., 2 weeks after veraison, however, it increased sharply from this point to 126 DAA (maturity). Exogenous ABA applications all resulted in an increase in berry skin ABA and anthocyanin concentration, irrespective of the developmental stage at which the treatment occurred (20 and 10 days pre-veraison, veraison or 7 days post-veraison), thereby advancing veraison. In contrast, resveratrol concentration increased only when ABA was applied at 10 days pre-veraison or at veraison. As a result, the accumulation of resveratrol was associated with veraison in grape berry skin and this accumulation, together with that of anthocyanins, was associated with ABA concentration. The response of resveratrol biosynthesis in the berry skin to manipulation of ABA varied during berry development and was less sensitive to ABA than the response of anthocyanin biosynthesis.